Hazel leaf polyphenols ameliorate hyperuricemia-induced renal fibrosis through regulating uric acid metabolism and inhibiting ferroptosis via the Nrf2/GPX4 signaling axis - Xinhe Wang; Xiaowen Li; Jiarui Zhao; Zhi Lin; Jun Li; Xinyi Xu; Xinrui Zhou; Yuchen Wang; Guangfu Lv; He Lin; Zhe Lin (Journal of Functional Foods)
Hazel leaves, a by-product of hazelnut, have been consumed for health care in some countries and regions for hundreds of years. Based on our previous results, this study further investigated the protective effects of hazel leaf polyphenols (HP) on renal fibrosis induced by hyperuricemia in mice. Results showed that they significantly reduced serum UA, BUN and CRE contents, inhibited liver XOD activity. Histological examination and Western blot analysis revealed that they renal pathological changes and fibrosis were obviously improved after HP administration. Additionally, combined with TEM, they attenuated oxidative stress and mitochondrial damage, and inhibited ferroptosis by regulating the expression of related proteins. Molecular docking predicted that chlorogenic acid, p-coumaric acid, luteolin, myricetin and kaempferol may be the key active ingredients. In conclusion, HP ameliorated hyperuricemia-induced renal fibrosis through regulating uric acid production, reabsorption and excretion, and inhibiting ferroptosis through Nrf2/GPX4 signaling axis. It provides a valuable basis for the utilization of hazel leaf polyphenols as health agents in the future.